If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -16 = 29 + 12x Reorder the terms: -16 + 15x = 29 + 12x Solving -16 + 15x = 29 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -16 + 15x + -12x = 29 + 12x + -12x Combine like terms: 15x + -12x = 3x -16 + 3x = 29 + 12x + -12x Combine like terms: 12x + -12x = 0 -16 + 3x = 29 + 0 -16 + 3x = 29 Add '16' to each side of the equation. -16 + 16 + 3x = 29 + 16 Combine like terms: -16 + 16 = 0 0 + 3x = 29 + 16 3x = 29 + 16 Combine like terms: 29 + 16 = 45 3x = 45 Divide each side by '3'. x = 15 Simplifying x = 15
| 27-3(9)+(7-4)b=24b | | 5t-4+3t=4(2t-1) | | x+x*0.12=6273.53 | | -7(x+2)-16=18+1 | | X+(2x-3)=72 | | 3+(15-1)(-4/3) | | 5y-2=29-4y | | 6=6+y | | 5(-3+7x)=-330 | | x+x*0.09=1000 | | 2(0.3r+1)=24 | | x-1/3=4/3 | | 5x+1=43-2x | | 2x^2+5x+6=x^2 | | 21x-16y=120 | | 10x-42+17x=13+14 | | .0855t^2-.916t+1.737=0 | | 8+2t-2=7t+8-4t | | 3(X+2)(X+2)+16(X+2)+5= | | 3+(5x-6/4) | | 3mx-9y=2(m+2b) | | x-7=144 | | 4s^2+16s-as-4a= | | 2/3(3/5) | | (5/6)t+4=(1/6)t-2 | | 13x+3x-5=27 | | .0825t^2-.886t+1.752=0 | | 5x-15=x+25 | | -x^2+11=0 | | -8+x/8=-12 | | 6(6x+5)=-390 | | (10)+c^3/3=c^3/(3)+10 |